1975
DOI: 10.1139/v75-077
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of Hydroperoxides with Triphenylarsine and Triphenylstibine

Abstract: R. H I A~, CHRISTINE MCCOLEMAN, and G. R. HOWE. Can. J. Chem. 53,559 (1975). Triphenylstibine reduced r-Bu02H to r-BuOH almost as fast as Ph3P does, while triphenylarsine reacts only 1/60as fast. Both reductions are first-order ineach component; in ethanol k, for Ph3Sb and Ph3As are 106.7e-9.71RT and 109.1e-15.7RT; respectively. The reductions are not very sensitive to choice of solvent, but are strongly catalyzed by compounds of molybdenum and vanadium.The relative rate order PH3P 3 Ph3Sb > Ph3As is ascribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 8 publications
(11 reference statements)
2
3
0
Order By: Relevance
“…For the series of Ph3M compounds ( = P, As, Sb), we have observed that the reactivity with tert-butyl hydroperoxide decreases in the order triphenylphosphine (entry 8) > triphenylstibine (entry 18) > triphenylarsine (entry 17). During the course of our work, Hiatt et al 15 published similar rate constants for this series and also noted the anomaly of triphenylstibine reactivity. If one considers the reaction with tert-butyl hydroperoxide as a series of nucleophilic attacks on a soft electrophile, the antimony derivative is out of line, i.e., the reactivity order should be P > As > Sb.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…For the series of Ph3M compounds ( = P, As, Sb), we have observed that the reactivity with tert-butyl hydroperoxide decreases in the order triphenylphosphine (entry 8) > triphenylstibine (entry 18) > triphenylarsine (entry 17). During the course of our work, Hiatt et al 15 published similar rate constants for this series and also noted the anomaly of triphenylstibine reactivity. If one considers the reaction with tert-butyl hydroperoxide as a series of nucleophilic attacks on a soft electrophile, the antimony derivative is out of line, i.e., the reactivity order should be P > As > Sb.…”
Section: Resultssupporting
confidence: 72%
“…However, triisopropyl (entry 13) and tri-2-ethylhexyl (entry 14) phosphites react with tertbutyl hydroperoxide more slowly than would be predicted by inductive effects alone, which suggests that steric factors do play a part in this reaction. During the course of our work, Hiatt et al 15 published similar rate constants for this series and also noted the anomaly of triphenylstibine reactivity. Using the Yukawa-Tsunol3 treatment to blend fractional amounts of g+ into the relationship does not improve the straight-line fit.…”
Section: Results a N D Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This fact confirms that the antimony atom in triphenylantimony o-phenylenedioxide is not accessible, and the coordinate Sb -O(P) bond formation is likely to take place at the earlier reaction step. Taking into account the corresponding rate constants for the reactions of triphenylphosphine and triphenylantimony with tert-butyl hydroperoxide, 21 we might suppose that the bond formation occures at the stage of antimony and phosphorus adducts (type 1) or when the oxygen of triphenylphosphine oxide coordinates to the antimony atom in triphenylantimony.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of the oxidation has been reported [9,10]. Ph 3 Sb forms either triphenylantimony diacetate Ph 3 Sb(OAc) 2 10 in the AcOH solution in the presence of hydroperoxide 3 (Eq.…”
Section: Transfer Of the Second Phenyl Groupmentioning
confidence: 99%